Desain Pengembangan Sistem Informasi Akuntansi oleh Pengguna - Ahmad Yani (LPPM Universitas Bina Sarana Informatika, 2021)
Abstract - Will never denied next that technology growth in area of informatics have brought which are positive change impact in so many area. One of them is in the field of Akuntansi . With our Information Technology utilization can easily modification and develop Information system Akuntansi that will produce finance information that very with quality. Existing process in Information system cycle Akuntansi can very efesien, practical and effective. Ada much Information system examples Akuntansi that have been designed base on Information Technology like DEA, Myob, Vplus, Zahir, MAS and others. Matter the most draw besides example of software product Accounting mentioned, we also can develop it by it self to the needs . Of course required ability requirement to be able to conduct it. Besides understand hit accountancy is also required knowledge addition in the field of Information Technology (system analysis, programing). Design and Accounting information system development that developed by it self by user (End user Development/ End user Computing) will have value very high utilitas because developer of know precisely need that must fulfilled by system that will be made. The research method used in this research is qualitative with a case study approach of an accounting information system. The final results of this study provide discourse and inspiration and solutions in the development of computer-based Accounting Information Systems. Keywords: End User Computing, Informatian System Accounting.